Factor structure of the Mini‐Maternal Behavior Q‐Sort and associations with infant attachment: Informing precision in research and intervention. (4th November 2022) - Booth, Anna T.; Greenwood, Christopher J.; Youssef, George J.; McIntosh, Jennifer E.; Nguyen, Thy; Letcher, Primrose; Edwards, Ben; Hutchinson, Delyse M.; Sanson, Ann; Olsson, Craig A.; Macdonald, Jacqui A.
Abstract: We examined the factor structure of parental sensitivity to infants as assessed by the Mini‐Maternal Behavior Q‐Sort (Mini‐MBQS), a 25‐item short‐form of the original 90‐item MBQS. We aimed to: (1) identify latent factors of the Mini‐MBQS; and (2) validate each factor by testing associations with infant attachment classifications. Data on parent‐infant dyads ( n = 313; 222 mothers with 281 children, 29 fathers with 32 children) were drawn from a three‐generation Australian cohort study. Exploratory Factor Analysis and Exploratory Structural Equation Modelling examined the structure of the Mini‐MBQS. Two latent Mini‐MBQS factors were identified, requiring 8 of 25 original items: (1) Attention and Responsiveness and (2) Contingency in Interactions. Infants with insecure attachment classifications had parents with lower sensitivity across both factors relative to infants classified secure. In particular, infants with resistant attachment classifications had parents with notably low Contingency in Interactions scores. Infants with disorganised attachment classifications had parents with the lowest relative sensitivity across both factors, and in these dyads Attention and Responsiveness scores were especially low. Results provide an empirically derived factor structure for the Mini‐MBQS. Two subscales, each with significant infant attachment associations, may improve precision in clinical intervention and research translation.